Time-resolved X-ray and XUV based spectroscopic methods for nonadiabatic processes in photochemistry. Issue 92 (1st November 2022) - Schnappinger, Thomas; Jadoun, Deependra; Gudem, Mahesh; Kowalewski, Markus
Abstract : Novel spectroscopic techniques based on ultra-short laser pulses in the X-ray regime are reviewed, capable of observing clear signatures of conical intersections. Abstract : The photochemistry of numerous molecular systems is influenced by conical intersections (CIs). These omnipresent nonadiabatic phenomena provide ultra-fast radiationless relaxation channels by creating degeneracies between electronic states and decide over the final photoproducts. In their presence, the Born–Oppenheimer approximation breaks down, and the timescales of the electron and nuclear dynamics become comparable. Due to the ultra-fast dynamics and the complex interplay between nuclear and electronic degrees of freedom, the direct experimental observation of nonadiabatic processes close to CIs remains challenging. In this article, we give a theoretical perspective on novel spectroscopic techniques capable of observing clear signatures of CIs. We discuss methods that are based on ultra-short laser pulses in the extreme ultraviolet and X-ray regime, as their spectral and temporal resolution allow for resolving the ultra-fast dynamics near CIs.